2018
DOI: 10.1016/j.chiabu.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal interventions for mothers and fathers who are survivors of childhood sexual abuse

Abstract: Childhood sexual abuse (CSA) is a worldwide problem with severe long-term consequences. A history of CSA can impact the childbearing experience of mothers and fathers; affecting their mental health, parenting skills and compromising infant development. Nonetheless, the perinatal period offers huge opportunity for intervention and hope. This literature review collates evidence for perinatal psychosocial interventions targeting both mothers and fathers who are survivors of CSA. Publications dating from 1970 to J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 74 publications
1
24
0
Order By: Relevance
“…First, we identified very few prenatal interventions specifically designed for expectant women and men who have personal histories of abuse or neglect, despite the long-term and intergenerational consequences associated with these adverse childhood experiences. 39 Second, our results confirm that health care providers and community organizations consider such an intervention important and a valuable addition to the services they already offer to victims of abuse or expectant parents. Third, the mentalization framework should be considered when developing such a program, with actions aimed at supporting participants' mentalization of their experience of parenthood and mentalization of their adverse childhood experiences.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…First, we identified very few prenatal interventions specifically designed for expectant women and men who have personal histories of abuse or neglect, despite the long-term and intergenerational consequences associated with these adverse childhood experiences. 39 Second, our results confirm that health care providers and community organizations consider such an intervention important and a valuable addition to the services they already offer to victims of abuse or expectant parents. Third, the mentalization framework should be considered when developing such a program, with actions aimed at supporting participants' mentalization of their experience of parenthood and mentalization of their adverse childhood experiences.…”
Section: Discussionsupporting
confidence: 71%
“…52 Several prenatal programs have been designed for at-risk parents, and many have been shown to lead to significant improvement in parental functioning and to positive outcomes for children. 39,[52][53][54] However, to the best of our knowledge, few interventions specifically address the unique needs of parents with personal histories of trauma or use a theory of trauma as conceptual framework. Even parenting interventions aimed at preventing childhood maltreatment and trauma are rarely informed by trauma theories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…histories of childhood maltreatment, but a recent literature review confirmed that there is currently no perinatal intervention that considered the needs of men with histories of childhood maltreatment. 46 This is particularly surprising knowing that childhood maltreatment affects both men and women, that men play a crucial and distinctive role in child development, and that prevention of family violence requires programs reaching both women and men. 47 Contrary to our expectations, there was no direct association between prenatal attachment and childhood maltreatment.…”
Section: Discussionmentioning
confidence: 99%